2007
DOI: 10.1007/s10389-007-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of smoking prevention measures in adolescents

Abstract: Introduction In view of the serious health risks and high costs to the health care system of tobacco consumption, getting young people to avoid smoking is an important element of preventive health care. The aim of this study was to give an overview of the scientific literature on costeffectiveness in smoking preventive interventions within this age group. Methods A literature search was conducted in publicly available databases. Results Eight studies confirming the cost-effectiveness of those programmes were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The cost of an intervention can be divided by the resulting increase in QALYs to yield the cost required to produce one year of perfect health. For example, Rasch and Greiner's (2008) review of economic analyses of various adolescent smoking prevention strategies indicated that in most cases primary prevention cost less than 20,000 Euros per QALY gained, albeit with wide variations among the investigated programs. By focusing on the production of QALYs, cost-utility analysis enables comparisons among programs designed to prevent, treat, or ameliorate any kind of health problem, and is not limited to only comparing interventions addressing the same problematic behavior.…”
Section: Types Of Economic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of an intervention can be divided by the resulting increase in QALYs to yield the cost required to produce one year of perfect health. For example, Rasch and Greiner's (2008) review of economic analyses of various adolescent smoking prevention strategies indicated that in most cases primary prevention cost less than 20,000 Euros per QALY gained, albeit with wide variations among the investigated programs. By focusing on the production of QALYs, cost-utility analysis enables comparisons among programs designed to prevent, treat, or ameliorate any kind of health problem, and is not limited to only comparing interventions addressing the same problematic behavior.…”
Section: Types Of Economic Analysismentioning
confidence: 99%
“…However, this approach ignores the reality that many conditions can be addressed in multiple ways. For example, rates of cigarette smoking may be reduced by school-based prevention programs, prohibiting sales to minors, exposing a population to anti-smoking messages, or increasing taxes on tobacco products (Rasch & Greiner, 2008). Additionally, cost-effectiveness analyses as typically conducted provide comparatively simplistic information for the complex reality in which health policy decisions must be made.…”
Section: Solutions and Ways Forwardmentioning
confidence: 99%